(untitled) (Research, Society and Development, 2022)
Objective: To identify the repercussions of diabetes mellitus in hospitalized elderly people in relation to functional capacity. Methods: This is a cross-sectional, descriptive study with quantitative analysis. The data collected were sociodemographic, health conditions, functional capacity and those related to diabetes mellitus. To assess functional capacity, the Katz and Lawton scales were applied. The participants included in the study were elderly people aged 60 years or older and were hospitalized in the medical clinic unit of a university hospital in Brasília, Federal District. Results: A total of 25 participants were included, with a mean age of 70 years, most of them women, married or widowed, with incomplete primary education and income of one minimum wage. As for life habits, 92% did not perform any type of physical activity, 36% were ex-smokers and 28% used alcohol. It was observed that 60% of the elderly were dependent on the performance of basic activities of daily living and 92% were dependent on some of the instrumental activities in their daily lives. Conclusion: Most elderly people who participated in the present research showed some degree of impairment in carrying out basic self-care activities and in more complex activities, resulting in greater impairment of functional capacity, which directly impacts the care that diabetes mellitus requires, which can lead to greater chances of this population developing other complications related to diabetes mellitus due to impaired self-care capacity.